THE ROLE OF SELF-DIRECTED LEARNING IN SHAPING BEHAVIORAL LEARNING ATTITUDES AMONG TEACHER TRAINEES AT PURSAT PROVINCIAL TEACHER TRAINING COLLEGE - Voeng, Sokhkhan; Cheng, Monika; Kan, Leakhena; Heng, Udomphirun; Kong, Sam Ol (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
Self-directed learning is significant to empower learners to take ownership of their learning, particularly in fostering positive behavioral learning attitudes, enhancing autonomy, and improving academic performance. This study examines its impact on teacher trainees' behavioral learning attitudes by: (1) analyzing changes after self-directed learning intervention, (2) assessing its overall impact, and (3) exploring trainees’ perceptions of their experiences. In the research, the study involved 83 first-year teacher trainees. Data were collected through pre- and post-tests, a questionnaire, and focus group discussions. Quantitative data were analyzed using a Paired-Sample T-Test and Multiple Regression, while qualitative data underwent Thematic Analysis. Findings shown a significant improvement in behavioral learning attitudes following self-directed learning with Self-directed learning was found to be a significant predictor (B = .544, p < .001), indicating that higher levels of self-directed learning led to higher post-test scores in behavioral learning attitudes. The approach strongly influenced overall behavioral learning attitudes, as teacher trainees perceived it as enhancing their self-regulation, learning engagement, persistence, proactive learning, and help-seeking behavior. The study concludes that self-directed learning is an effective instructional approach for fostering positive behavioral attitudes. These findings suggest integrating self-directed learning model into teacher training programs to promote autonomy and engagement. Future research should examine its long-term effects on professional development.